2017
DOI: 10.4028/www.scientific.net/kem.751.344
|View full text |Cite
|
Sign up to set email alerts
|

Poly(Lactic Acid)-Polybutylene Succinate-Activated Carbon Composite Foams

Abstract: Polymer blends of poly (lactic acid) (PLA) and polybutylene succinate (PBS) containing activated carbon (AC) were foamed by using Azodicarbonamide (ADC) through an extrusion process. The composite foams containing 5 phr of AC had lower density than those without AC loading for PLA:PBS ratios of 90:10, 80:20, 70:30, and 60:40. The incident of higher void fraction was the consequences of more foaming nucleation centers which were induced by adding AC in the composite foam. Maximum reduction of density by 50% wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It was found that PLA/PBS (80/20) foamed at 100°C provides the highest cell opening rate (96%). Ketkul et al 23 disclosed a PLA-PBS-activated carbon (AC) composite foam by investigating various PLA/PBS ratios with fixed AC content (i.e. 5 phr).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that PLA/PBS (80/20) foamed at 100°C provides the highest cell opening rate (96%). Ketkul et al 23 disclosed a PLA-PBS-activated carbon (AC) composite foam by investigating various PLA/PBS ratios with fixed AC content (i.e. 5 phr).…”
Section: Introductionmentioning
confidence: 99%
“…Compression modulus of chitosan and cellulose-based foams that had different densities were determined to range from 10 to 1300 KPa (Wang et al 2017;Michailidou et al 2019;Ozen et al 2021) and 15 to 2800 KPa (Gibson and Ashby 1997;Liu et al 2017), respectively. In contrast, activated carbon-reinforced foam has been evaluated in few studies and could not notably enhance the mechanical properties of foams (Ketkul et al 2017). In another study, the compressive resistance of resol-type phenolic resin foam that was reinforced with activated carbon was improved by 30% (Song et al 2013).…”
Section: Resultsmentioning
confidence: 97%
“…Activated carbon aerogels derived from carboxymethyl cellulose could be used in energy storage applications [18]. The addition of activated carbon to poly(lactic acid)-polybutylene succinate foams enhanced their thermal and mechanical properties [19]. In the last few decades, activated carbon has started to be studied in fiberboard production.…”
Section: Introductionmentioning
confidence: 99%